STREAMFLOW CHANGES OVER SIBERIAN YENISEI RIVER BASIN - Yang D.; Kane D.L.; Ye B. (My University, 2004)
This study analyzes long-term (1935–99) monthly discharge data for the major sub-basins within the Yenisei River watershed in order to document significant streamflow changes induced by reservoir regulations and by natural variations/changes. The results show that both the unregulated upper basin and major lower streams of the watershed experienced streamflow decreases in the early melt period and discharge increases in the late melt season. These changes in snowmelt runoff pattern suggest a delay in snowcover melt in the Yenisei basin perhaps associated with cooling trends during the snowmelt months over central Siberia. This study also demonstrates that the reservoir regulation has significantly altered the monthly discharge regimes in northeast and the upper portions of the Yenisei basin. Constructions of four large dams in the northeast Yensiei regions reduced the summer peak flows in the Angara valley by 15–30% and increased the winter low flows by 5–30%. Operations of two large reservoirs in the upper Yenisei regions enhanced the winter flows by 45–85% and reduced the summer flows by 10–50%. These alterations lead to a streamflow regime change toward less seasonal variation over the eastern and lower Yenisei basin. Because of reservoir regulations, discharge records collected at the Yenisei basin outlet do not always represent natural changes and variations, they tend to underestimate the natural streamflow trends in summer and overestimate the trends in winter and fall seasons. Cold season discharge increase over the Yenisei river is not natural-caused, but mainly the effect of reservoir regulations in the Yenisei basin.
Keywords: Streamflow; Regime and change; Dams; Yenisei river; Siberia